Designing a Green Management Model in Iranian Sports Organizations - Kiani, Mohammad Saeid; Nazari , Leila (International Journal of Economics, Management and Accounting, 2025)
Today, organizations can properly play their role by focusing on economic responsibility and organizational wealth creation, in line with their social and environmental responsibilities. Adopting such an approach, known as the green approach, will enable the organization to achieve its economic goals. The term green human resource management (GHRM) was introduced in 1990 and has been accepted worldwide since 2000 as a concept that manages the environment within an organization by adopting green human resource policies and practices. The present study aimed at designing a GHRM model in Iranian sports organizations. This research is applied in terms of purpose and descriptive survey in terms of nature and method. The population of the study consists of experts and managers of the Ministry of Sports and Youth of Iran, 70 of whom were selected using purposive sampling. The data collection tool was a researcher-made questionnaire with validity confirmed using the content validity method. The research findings in the form of a model consist of two parts: First, through an exploratory study and expert opinion, 14 main factors of GHRM success were identified. Second, using an interpretive-structural modeling approach, relationships and sequences between variables were extracted at eight levels and finally categorized based on the degree of influence and dependence. Considering the results and also the importance and necessity of GHRM, it is suggested that organizations, especially sports organizations, pay special attention to GHRM and by using its policies and strategies, be able to achieve goals and align their activities well with environmental goals. The results showed that the support of the environment around the organization and the support of managers and shareholders act as the foundation stone of the model and have the greatest impact on other variables and cause intensification of other variables to manage organizational green human resources. This model can help managers efficiently and effectively use natural resources by applying green HRM methods and strategies.